Dose-dependent regulation of horizontal cell fate by Onecut family of transcription factors - Kreplova, Michaela; Kuzelova, Andrea; Antosova, Barbora; Zilova, Lucie; Jägle, Herbert; Kozmik, Zbynek (PLoS One, 2020)
Genome duplication leads to an emergence of gene paralogs that are essentially free to undergo the process of neofunctionalization, subfunctionalization or degeneration (gene loss). Onecut1 (Oc1) and Onecut2 (Oc2) transcription factors, encoded by paralogous genes in mammals, are expressed in precursors of horizontal cells (HCs), retinal ganglion cells and cone photoreceptors. Previous studies have shown that ablation of either Oc1 or Oc2 gene in the mouse retina results in a decreased number of HCs, while simultaneous deletion of Oc1 and Oc2 leads to a complete loss of HCs. Here we study the genetic redundancy between Oc1 and Oc2 paralogs and focus on how the dose of Onecut transcription factors influences abundance of individual retinal cell types and overall retina physiology. Our data show that reducing the number of functional Oc alleles in the developing retina leads to a gradual decrease in the number of HCs, progressive thinning of the outer plexiform layer and diminished electrophysiology responses. Taken together, these observations indicate that in the context of HC population, the alleles of Oc1/Oc2 paralogous genes are mutually interchangeable, function additively to support proper retinal function and their molecular evolution does not follow one of the typical routes after gene duplication.
Keywords: Animals; myši transgenní; Genetic Loci; Genotype; Hepatocyte Nuclear Factor 6; retinální gangliové buňky; transkripční faktory; Mice, Transgenic; Retina; hepatocytární jaderný faktor 6; bipolární buňky sítnice; Retinal Ganglion Cells; Mice; genotyp; Transcription Factors; homeodoménové proteiny; amakrinní buňky; Amacrine Cells; Ependymoglial Cells; Retinal Bipolar Cells; myši; oči; Eye; Homeodomain Proteins; alely; Retinal Cone Photoreceptor Cells; Alleles; retina; zvířata; čípky retiny; genetické lokusy; ependymální buňky